TAṬWÎR KITĀB AL-QIRĀ’AT AL-RASYÎDAH LI TARQIYYAH MAHĀRAH AL-QIRĀ’AH ‘INDA AL-ṬĀLIBAH BI ISTIKHDĀM AL-KITĀB AL-ELEKTRÛNY AL-TAFĀ’ULIY FI AL-MADRASAH AL-MUTAWASSIṬAH INSĀN QUR’ĀNY ACEH BESAR - Muslim, Buhori; Zikrina, Zikrina; Mukhlisah, Mukhlisah (Islam Futura, 2023)
Based on the research problem, which is the teaching of reading skills using the book "Al-Qira'ah al-Rasyidah" at MTs Insan Qur'ani, it is observed that the use of modern electronic instructional materials aligned with the advancements in digital technology to deliver content in accordance with the demands of the industrial revolution 4.0 era has not been incorporated. The purpose of this research is to investigate and develop the "Al-Qira'ah al-Rasyidah" instructional book using an Interactive E-Book to enhance the reading skills of female students and assess the effectiveness of its implementation. The research instruments encompass interviews, questionnaires, and tests based on Borg and Gall's theory. The research subjects consist of 28 students from class VII-C (grade 1 of MTs) at MTs Insan Qur'ani for the academic year 2022-2023. The findings reveal that the development of the "Al-Qira'ah al-Rasyidah" book for reading instruction using an Interactive E-Book is highly effective. In the final test conducted, the students achieved a total score of 2259 with an average score of 80.67, surpassing the Minimum Mastery Criteria (KKM) for reading skills, which is set at >75.